INTERAKSI SOSIAL MAHASISWA SOSIOLOGI (Studi Kasus Mahasiswa Antar Daerah di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau) - Sakti, Ferlita Kencana; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study entitled "Social Interaction of Sociology Students (Case Study of Inter-Regional Students at the Faculty of Social and Political Sciences, Riau University). This study aims to determine the forms of social interaction that occur between students between regions in the Sociology department. Starting from the form of cooperation to competition between students between regions. The method used in this research is descriptive qualitative research method with purposive sampling technique, which determines the criteria to determine the research informants. Researchers determined 7 people as research informants, 2 men, 5 women, 3 students from Riau, 2 students from West Sumatra and 2 students from North Sumatra. The findings in this study are that researchers can find out the forms of cooperation and competition that occur between sociology students between regions. The results of the research were the existence of a cooperative attitude of help in terms of borrowing money, borrowing textbooks, confiding in, asking for help to move boarding houses, asking for a shuttle to campus, studying together, participating in organizations that occurred between sociology students between regions and competing in achievement. status in the organization to scholarship, although competing, it does not cause significant conflict because the competition here is fair and healthy. Keywords : Social Interaction, Cooperation, Competition